Investigation of memory-enhancing botanical mixture and their isolated compounds for inhibition of amyloid-beta and tau aggregation - Baek, Seungyeop; Park, Sohui; Shin, Jisu; Lee, Jun-Seok; Kim, Hye Yun; Han, Gyoonhee; Kim, YoungSoo (한국응용생명화학회, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by the abnormal assembly of amyloid-beta (A beta) and tau aggregates in the brain. When A beta and tau proteins misfold, progressive brain cell death, synaptic loss, atrophy, and cognitive decline are observed. Here, we report that the memory-enhancing botanical natural product mixture, HX106N, efficiently inhibits formation of A beta oligomers and fibrils and aggregation of tau. HX106N is a botanical mixture extract of Dimocarpus longan, Liriope platyphylla, Salvia miltiorrhiza and Gastrodia elata. In previous clinical studies, HX106N showed increased working memory performances of individuals of subjective memory complaints. However, the drug mechanism and responsible ingredients of HX106N has been unclear yet. In this study, we expanded the investigation of the drug mode of action to the single chemical level by identifying four active components of HX106N, among 14 isolated molecules, with significant inhibitory function against A beta aggregation. We found that salvianolic acids A, B, E and rosmarinic acid, isolated from the botanical mixture, have potency to inhibit the protein misfolding.